Perceived stress in women with metabolic syndrome: a cross-sectional study - Santos Barros, Vinicius; Alves de Araújo, Wilkslam; Vinicius Santos de Jesus, Marcos; de Oliveira Damaceno, Taynnan; Montargil Rocha, Roseanne; Dumêt Fernandes, Josicélia; Souza Rosa, Randson; Santana Cardoso Santos, Isleide (Revista Cuidarte, 2023)
Introduction: Perceived stress has been suggested as a risk factor for the development of Metabolic Syndrome (MS). However, little is known about this association among women. Objective: to evaluate perceived stress in women with Metabolic Syndrome (MS). Materials and Methods: cross-sectional study, based on a non-randomized clinical trial, with patients from a public health center (RBR-43K52N). The outcome variable was MS, using the NCEP/ATPIII criteria. Sociodemographic, anthropometric, biochemical, hemodynamic data and PSS application were collected. Results: The sample consisted of 75 women affected by MetS (47.69± 8.15 years old; 155.65±0.07 cm; 82.43±17.79 kg; BMI of 33.96±6 ,42). High WHR values were found among stressed and non-stressed women. The average PSS score was 27.73±9.17. In the groups, there was a significant difference for PSS between stressed and non-stressed women (35.24±5.22 and 20.42±5.53, respectively; p=0.001). It was also observed that stressed women had higher levels of triglycerides and lower levels of HDL-c when compared to non-stressed women, although without statistical difference. Discussions: The findings suggest that women categorized as stressed had higher PSS scores, higher levels of triglycerides and lower levels of HDL-c when compared to non-stressed women. Conclusions: the PSS score was significantly higher among women with altered MS lipid parameters, with lower levels of HDL- and increased triglycerides.How to cite this article: Barros, Vinicius Santos; de Araújo, Wilkslam Alves; de Jesus, Marcos Vinicius Santos; Damaceno, Taynnan de Oliveira; Rocha, Roseanne Montargil; Fernandes, Josicélia Dumêt; Rosa, Randson Souza; Santos, Isleide Santana Cardoso.  Estresse percebido em mulheres com síndrome metabólica: um estudo transversal. Revista Cuidarte. 2023;14(1):e2634. http://dx.doi.org/10.15649/cuidarte.2634
Keywords: Metabolic Syndrome; Dyslipidemias; Obesity, Abdominal; Women